Keperluan Prosedur Operasi Standard Dalam Penerimaan Dokumen Digital Di Mahkamah Sivil Malaysia - Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Lukman Abdul Mutalib; Nurul Syazwani Abdullah Kahar (UUM Journal of Legal Studies (UUMJLS), 2024)
Indexed by Scopus/MyCite